FEED CONVERSION RATIO OF MAJOR CARP CIRRHINUS MRIGALA FINGERLINGS FED ON COTTON SEED MEAL, FISH MEAL AND BARLEY - S. Jabeen, M. Salim and P. Akhtar1 (Pakistan Veterinary Journal, 2004)
A six-week experiment was conducted in six glass aquaria to study the feed conversion ratio (FCR) of Cirrhinus mrigala fingerlings fed on cotton seed meal (35.69% CP), fish meal (50.41% CP) and barley (9.98% CP). The ingredients were supplied at the rate of 4% of wet body weight of fingerlings twice a day. Twenty fingerlings were randomly stocked in each aquarium. The Cirrhinus mrigala fingerlings gained highest average body weight on fish meal (1.23g), followed by cotton seed meal (1.17g) and barley (0.55g). FCR calculated for three treatments was highest for barley (2.59), followed be fish meal (2.02) and cotton seed meal (1.55). The correlation coefficient between average body weight and FCR values was significant and positive in case of cotton seed meal and fish meal, whereas it was positive and non significant in case of barley.